Strategi Peningkatan Mutu Pelayanan Publik melalui Inovasi Digital di Kelurahan Sunter Agung - Anugrah Diastuti; Rissa Ayyustia (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to analyze the strategy of improving the quality of public services through digital innovation in Sunter Agung Urban Village. In the era of globalization and rapid development of information technology, public services are expected to be more responsive, transparent, and efficient. The research used a descriptive qualitative approach with data collection through documentation studies and in-depth interviews with urban village officials and service users. The results showed that the use of digital innovations such as web-based service applications, online queuing systems, and document digitization has had a positive impact on improving service quality, including accelerating administrative processes and increasing community satisfaction. However, various obstacles are still found, including limited network infrastructure, suboptimal human resource capacity in mastering technology, and low digital literacy among the community, especially the elderly. For this reason, the proposed quality improvement strategy includes strengthening institutional capacity through digital training for apparatus, developing technological infrastructure, and digital literacy campaigns involving the wider community. This research is expected to serve as a reference for local governments in developing inclusive and sustainable digital-based public services.